2013
DOI: 10.5897/jeif2013.0489
|View full text |Cite
|
Sign up to set email alerts
|

Public expenditure and economic growth nexus: Further evidence from Nigeria

Abstract: This paper examines the relationship between public expenditure and economic growth in Nigeria during the period 1970-2009. A disaggregated public expenditure level was employed using the Gregory-Hansen structural breaks cointegration technique. The result confirms Wagner's law in two models in the long run; there was a break in 1993 in which the political crisis that engulfed the nation was accountable. The result also shows that economic growth and development are the main objectives of government expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…This is particularly true for developing countries where evidence of the positive growth effect of government expenditure can be found in earlier empirical studies conducted by [10,59]. These findings have been strengthened and supported subsequently by many studies including, [60,61,62,63]; etc.…”
Section: Neither Wagner Nor Keynesian Hypothesismentioning
confidence: 68%
“…This is particularly true for developing countries where evidence of the positive growth effect of government expenditure can be found in earlier empirical studies conducted by [10,59]. These findings have been strengthened and supported subsequently by many studies including, [60,61,62,63]; etc.…”
Section: Neither Wagner Nor Keynesian Hypothesismentioning
confidence: 68%
“…Results of the study showed that in the short run public spending had no impact on growth, but in the long run, a relationship was established between the two variables. Oyinlola and Akinnibosun (2013) examined the relationship between public expenditure and economic growth in Nigeria during the period 1970-2009. After confirming the Wagner's law, the result of the study further showed that economic growth and development were the main objectives of government expenditure, especially investment in infrastructure and human resources all of which fall under social and community services.…”
Section: Review Of Government Spending and Growth Nexusmentioning
confidence: 99%
“…For instance, Oyinlola and Akinbosun [4] used data over a period between 1970 and 2009 inclusive and employed disaggregated public expenditure data to confirm the validity of Wagner's law in the end. So also, Ayo, Ifeakachukwu and Ditimi [5] when employed data from 1970 to 2010 confirmed bidirectional relationship between the government expenditure and economic growth in the end, but in the short-run only wagner's law is established which supports the argument that growth is exogenous to expenditure in Nigeria, although they employed inflation as a third variable in their analysis.…”
Section: Introductionmentioning
confidence: 99%